HUBUNGAN KARAKTERISTIK SUAMI DENGAN DUKUNGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KEDUNGUTER KECAMATAN BANYUMAS KABUPATEN BANYUMAS TAHUN 2013 - Susilo Rini; Diannike P (Viva Medika, 2015)
Exclusive breastfeeding in the Banyumas a decline of 53.6% in 2011 to 49.9% in 2012.That's because the husband's lack of support exclusive breastfeeding. If fathers support and knowthe benefits of exclusive breastfeeding rate reached 98.1%. Otherwise without the support of herhusband, the success rate of exclusive breastfeeding was 26.9%. This study aims to determine the characteristics of the relationship with the husband'ssupport exclusive breastfeeding in rural areas Kedunguter Banyumas district in 2013. This study was an observational study with a correlational design with cross sectionalapproach. Sampling tec hnique in this study uses total sampling, the study sample were marriedcouples who have a baby with a good 0-6 months of exclusive breast-fed and non- breast fedexclusively by 30 couples. Questionnaires measuring instruments used and the type of data is theprimary data. Data analysis using chi-square. There is a significant correlation between the age of husband, education and knowledge tosupport exclusive breastfeeding in the Village Kedunguter Banyumas district Banyumas in 2013with a value of ?-value <a and there is no significant relationship between the husband's job tosupport exclusive breastfeeding in the Village District Kedunguter Banyumas Regency Banyumas in2013 with a value of ?- value> a . Keywords : Characteristics, Husband, Support, exclusive breastfeeding